ANALISIS DAMPAK EFEK BERGANDA PADA PANTAI SUWUK DI DESA TAMBAK MULYO KECAMATAN PURING KABUPATEN KEBUMEN - Rohyani, Indah; Noorsanti, Dewi; Nur Azizah, Siti; Wahyuningsih, Sri (ANALISIS FAKTOR-FAKTOR PENYEBAB TERJADINYA KREDIT MACET PADA KUD RAHMAT WIDODO KECAMATAN SRUWENG KABUPATEN KEBUMEN, 2019)
Suwuk Beach is one of the leading coastal tourism destinations in Kebumen Regency. In 2018 Suwuk beach is still an attractive destination for tourists with 287,085 tourists. This can bring economic benefits to the people in the Suwuk coastal area. To determine the impact of the economy, the researchers used a multiplier effect formula. The results found in this study are the multipliyer's effect on type I and II, namely Multiplier Effect 2.44, Keynesian Local Income Multiplier 1.2 and Ratio Income Multiplier of 1.6 so that tourism activities have an economic impact on people's income.